2006
DOI: 10.1590/s1679-87592006000300003
|View full text |Cite
|
Sign up to set email alerts
|

Distribution and abundance of Cladocera (Branchiopoda) in the Paraíba do Sul River estuary, Rio de Janeiro, Brazil

Abstract: To characterize the cladoceran community of the Paraíba do Sul River estuary, located in the district of São João da Barra, Rio de Janeiro, Brazil, cladocerans were collected monthly in nine sampling stations from September 2002 until August 2003. Samples were obtained by subsurface tows using a plankton net with a 30 cm opening mouth and 70 micron mesh size, fitted with a mechanical flowmeter. Environmental parameters such as salinity and temperature were also obtained. Seventeen species of Cladocera were ide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
14
0
3

Year Published

2008
2008
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 16 publications
3
14
0
3
Order By: Relevance
“…Freshwater, brackish and marine zooplankton communities, similar to those observed in the Grand Lahou lagoon, have been described in other brackish water environments, as for example the Ebrié Lagoon in Côte d'Ivoire (Arfi et al, 1987); the river Paraiba do Sul estuary in Rio de Janeiro, Brazil (Sterza & Fernandes, 2006) and the Pô River delta in Italy (Ferrari et al, 1982). Taxa from the freshwater community have been already reported in some freshwater ecosystems in Côte d'Ivoire (Yté et al 1996;Aka et al 2000) or in other West African countries as Senegal (Kâ et al, 2006) and Nigeria (Egborge, 1994).…”
Section: Discussionmentioning
confidence: 54%
“…Freshwater, brackish and marine zooplankton communities, similar to those observed in the Grand Lahou lagoon, have been described in other brackish water environments, as for example the Ebrié Lagoon in Côte d'Ivoire (Arfi et al, 1987); the river Paraiba do Sul estuary in Rio de Janeiro, Brazil (Sterza & Fernandes, 2006) and the Pô River delta in Italy (Ferrari et al, 1982). Taxa from the freshwater community have been already reported in some freshwater ecosystems in Côte d'Ivoire (Yté et al 1996;Aka et al 2000) or in other West African countries as Senegal (Kâ et al, 2006) and Nigeria (Egborge, 1994).…”
Section: Discussionmentioning
confidence: 54%
“…Derry et al (2003) found that in Canadian shallow lakes with chloride waters, B. plicatilis and the hapacticoid copepod Cletocampus sp., were the dominant species. However, it cannot be claimed that some abundant species such as Moina micrura and Metacyclops mendocinus should be considered indicators of a narrow range of salinity or a limited ionic concentration because they generally show a relatively wide range of tolerance (Rzóska, 1961;Alonso, 1996;Sterza and Fernández, 2006;Santangelo et al, 2008;Brucet et al, 2009).…”
Section: Zooplankton Featuresmentioning
confidence: 99%
“…Estuaries as transition areas between land and sea form aquatic ecosystems that are characterized as one of the most dynamic ecosystems by a variety of inter-related biotic and abiotic structural components and intensive chemical, physical and biological processes which influence species density and diversity (Aslan-Yılmaz et al, 2004;Telesh, 2004;Yüksek et al, 2006;Sterza and Fernandes, 2006;Sun et al, 2009). …”
Section: Introductionmentioning
confidence: 99%
“…Because of the unusual dynamic conditions experienced in estuaries zooplankton distribution is spatially and temporally heterogeneous, more so than in other aquatic ecosystems (Kibirige and Perissinotto, 2003;Sterza and Fernandes, 2006). High primary production levels make estuarine zooplankton very abundant, however some other biological factors, like environmental variables, may restrict the variety of the zooplankton species when compared to that of the marine areas.…”
Section: Introductionmentioning
confidence: 99%